2005
DOI: 10.1161/01.cir.0000165147.99592.01
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Inotropic Reserve and Increased Susceptibility to Cardiac Ischemia/Reperfusion Injury in Phosphocreatine-Deficient Guanidinoacetate- N -Methyltransferase–Knockout Mice

Abstract: Background-The role of the creatine kinase (CK)/phosphocreatine (PCr) energy buffer and transport system in heart remains unclear. Guanidinoacetate-N-methyltransferase-knockout (GAMT Ϫ/Ϫ ) mice represent a new model of profoundly altered cardiac energetics, showing undetectable levels of PCr and creatine and accumulation of the precursor (phospho-)guanidinoacetate (P-GA). To characterize the role of a substantially impaired CK/PCr system in heart, we studied the cardiac phenotype of wild-type (WT) and GAMT Ϫ/Ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 42 publications
4
87
0
2
Order By: Relevance
“…This energy transfer system is not required during normal workload conditions but is necessary to achieve high-work states. Indeed, the heart is unable to function in the upper 50% of its dynamic range when CK is inhibited (4,8,11,24,27). Thus energy transfers via ADP-to-ATP ratio (ADP/ATP), which are sufficient to match low rates of energy production and consumption, represent an energy "leak" at high rates of cardiac work.…”
Section: Discussionmentioning
confidence: 99%
“…This energy transfer system is not required during normal workload conditions but is necessary to achieve high-work states. Indeed, the heart is unable to function in the upper 50% of its dynamic range when CK is inhibited (4,8,11,24,27). Thus energy transfers via ADP-to-ATP ratio (ADP/ATP), which are sufficient to match low rates of energy production and consumption, represent an energy "leak" at high rates of cardiac work.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A number of studies in both humans and animal models have all shown that phosphocreatine (PCr) and free creatine levels decrease by up to 60% to 70% in heart failure, independent of the underlying etiology but in relation to the severity of contrac-tile dysfunction. 9 -15 Impairment of high-energy phosphate availability in creatine kinase (CK)- 16 or in guanidinoacetate-N-methyltransferase 17 -knockout mice has adverse consequences for myocardial function. Failing hearts with an impaired CK system are unable to maintain low levels of free ADP and thus, high phosphorylation potential during inotropic stimulation.…”
Section: Clinical Perspective P 3139mentioning
confidence: 99%
“…These measurements were obtained, as previously described, 17 immediately after the 3D echocardiogram under the same general anesthesia, which was maintained with 2% isoflurane during cannulation. The right carotid artery was dissected and cannulated with a 1.4F microtipped pressure cannula (SPR-839, Millar Instruments), which was advanced retrogradely into the LV cavity under echocardiographic guidance.…”
Section: In Vivo LV Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they showed increased susceptibility to ischemic injury (46) and electrical instability during stress (47) as well as a markedly reduced work capacity during voluntary exercise (48). Mice with undetectable levels of creatine phosphate attributable to knock out of a critical enzyme required for creatine synthesis also had normal resting cardiac function but a markedly impaired inotropic reserve in response to adrenergic stimulation (49). In permeabilized cardiac muscle fibers from CK knockout mice, ATP generated endogenously by mitochondria was found to be much more effective at supporting SR Ca uptake (6) than exogenous ATP delivered via the bath, indicating that competition for exogenous ATP by other ATPases limited its availability to Ca ATPases in the SR.…”
Section: Perspective 2: Cardiovascular Metabolism As a Physical Spatmentioning
confidence: 99%